Effects of High-Intensity Resistance Training on Fitness and Fatness in Older Men With Osteosarcopenia - Kemmler, Wolfgang; Kohl, Matthias; Fröhlich, Michael; Engelke, Klaus; von Stengel, Simon; Schoene, Daniel (Frontiers in Physiology, 2020)
To date, there has been no study on the long-term effects of resistance exercise on sarcopenia and obesity indices for people with sarcopenia. The present study thus aimed to determine the effect of 18 months of periodized, high-velocity/intensity/effort progressive resistance training (HIT-RT) on body composition and strength in older men with osteosarcopenia. Using a single-blind, two-group parallel design, 43 community-dwelling men, 72 years and older, with osteopenia and sarcopenia in Erlangen-Nürnberg, Germany, were randomly assigned to two study arms by drawing lots: (1) an exercise group that conducted a consistently supervised periodized high-velocity/intensity/effort protocol (HIT-RT; n = 21) on machines twice a week for 18 months or (2) a control group (CG; n = 22) that maintained their physical activity/exercise habits. Both groups were supplied with protein, cholecalciferol, and calcium according to current recommendations. The study outcomes were lean body mass (LBM), total and abdominal body fat as determined by dual-energy X-ray absorptiometry and maximum hip/leg extensor strength as assessed on an isokinetic leg press at baseline and after 8, 12, and 18 months of follow-up. The intention-to-treat principle and multiple imputation were applied to calculated study outcomes. After 18 months of HIT-RT, altogether five participants were lost to follow up (HIT-RT: n = 2, CG: n = 3). The attendance rates (95%) for HIT-RT were high; relevant adverse effects were not observed. Significant effects (i.e., differences between HIT-RT vs. CG) in favor of HIT-RT were determined for LBM (+1.73 kg, 95% CI: +1.13 to +2.32 kg), total body fat mass (−2.44 kg, 95% CI: −1.28 to 3.60 kg), abdominal body fat percentage (−2.68, 95% CI: −1.70 to −3.66), and maximum hip/leg extensor strength (+533 N, 95% CI: +397 to +670 N; all p < 0.001). Even after adjusting for multiple testing, all effects remained significant. Of note, after 8 months of HIT-RT, only slight (LBM and fat indices) to moderate (maximum strength) ongoing effects were observed. Carefully introduced, continuously supervised HIT-RT is an effective, attractive, feasible, and safe method to improve body composition and muscle strength in older community-dwelling men with sarcopenia. However, even when consequently applying principles of exercise intensity progression within the RT protocol, only slight further positive changes were observed after 8 months of exercise.